We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
77
1
avatar+8 

x^2-5x=2(3-2x)

 Sep 19, 2019

Best Answer 

 #1
avatar+19822 
+2

Expand right side to get

 

x^2-5x = 6-4x      move r side to left side

x^2 -x-6=0            factor

(x-3)(x+2)=0

 Sep 19, 2019
 #1
avatar+19822 
+2
Best Answer

Expand right side to get

 

x^2-5x = 6-4x      move r side to left side

x^2 -x-6=0            factor

(x-3)(x+2)=0

ElectricPavlov Sep 19, 2019

25 Online Users

avatar